Langvinn berkjubólga hjá fimmtugum og áttræðum íslenskum körlum : algengi og lífsgæði - Sveinn Magnússon; Þórarinn Gíslason (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: The mortality from chronic bronchitis has been increasing in Iceland during the last decades. Little is however known about the prevalence of this disease and the objective of this study was to find the prevalence of chronic bronchitis in Iceland. Material and methods: In this study a postal questionnaire was sent to all Icelandic males born in the years 1913 (N=388) and 1943 (N=1297) who were alive on the 1st November 1993, asking about several physical symptoms, including symptoms of chronic bronchitis. The response rate was 69.7%. Results: Altogether 7.1% of 50 years old males and 16.7% of 80 years old males had a history of daily sputum expectoration for at least three months during the last two years. These individuals with chronic bronchitis had a higher prevalence of other respiratory symptoms, such as coughing, wheezing or whistling. History of dyspnea was much higher among those with symptoms of chronic bronchitis. They also complained more often of sleep disturbances and found themselves more stressed than those without symptoms of chronic bronchitis. Conclusion: Our study indicates that chronic bronchitis is a frequent illness among Icelandic males. Men with chronic bronchitis frequently have a decreased quality of life, difficulties to move and frequently sleep complaints. Tilgangur: Dánartíðni vegna langvinnrar berkjubólgu hefur farið vaxandi á Íslandi undanfarna áratugi. Lítið er aftur á móti vitað um algengi þessa sjúkdómsástands og tilgangur rannsóknarinnar var að kanna það. Efniviður og aðferðir: Í þessari rannsókn var öllum íslenskum karlmönnum sem fæddir voru árin 1913 (N=388) og 1943 (N=1297) og voru lifandi þann 1. nóvember 1993 sendar í pósti spurningar um ýmis líkamleg einkenni, þar á meðal einkenni um langvinna berkjubólgu. Svörun var 69,7%. Niðurstöður: Alls höfðu 7,1% 50 ára karla og 16,7% áttræðra sögu um daglegan slímuppgang í að minnsta kosti þrjá mánuði síðastliðin tvö ár. ...